PARTISIPASI DAN AKSI WARGA DALAM MEMBANGUN PLATFORM E-COMMERCE KOLABORATIF UNTUK PEMBERDAYAAN MASYARAKAT KAMPUNG LONTONG SURABAYA - Hendro Margono; Imam Yuadi; Yunus Abdul Halim; Ragil Tri Atmi; Indah Nur Maulidya; Berlian Savitri; Hilwah Hilwah; Ollyvia Pujasari Anggraini; Yasmina Sholihatunnisa; Muhammad Naufal Zaafarani (Jurnal Abdi Insani, 2026)
Kampung Lontong Surabaya has great potential as a unique destination known for its traditional lontong production center. Despite this potential, the community faces challenges in business digitalization. The main problems include limited knowledge of UMKM regarding business management integrated with digital concepts and the use of digital platforms. To address this, efforts were made through community empowerment, particularly by developing and optimizing a website as a digital promotion medium. The community service team applied the Participatory Action Research (PAR) method, emphasizing active participation of residents in every stage. Activities included socialization, mentoring, and training on e-commerce websites and social media through three sessions, followed by competitions that promoted local events and culinary tourism in Kampung Lontong. The final stage consisted of periodic monitoring and evaluation to ensure sustainability. As a result, residents’ knowledge is now documented and distributed through digital media, strengthening their capacity in managing online promotional tools. The program not only produced tangible outputs but also created opportunities for collaboration with external partners such as media and educational tourism networks. Moreover, it successfully reactivated the role of community associations as collective actors in developing Kampung Lontong as a digitally adaptive community.